A universal dimensionless length scale in medium range order amorphous structures. (15th June 2022) - Shukla, Pragya
Abstract: Our theoretical analysis reveals the existence of a previously unknown universality, namely, a dimensionless length scale, related to a ratio of medium and short range order structures of amorphous systems that originates from a conspiracy between dispersion forces among molecules and their phonon mediated coupling. The scale in turn gives rise to the structure lying underneath the low temperature universalities of many other properties e.g. specific heat, internal friction, boson peak characteristics, Meissner–Berret ratio etc.